Perceptions of food intake and weight status among parents of picky eating infants and toddlers in China: A cross-sectional study. (1st January 2017) - Li, Ziyi; van der Horst, Klazine; Edelson-Fries, Lisa R.; Yu, Kai; You, Lili; Zhang, Yumei; Vinyes-Pares, Gerard; Wang, Peiyu; Ma, Defu; Yang, Xiaoguang; Qin, Liqiang; Wang, Jiaji
Abstract: Background: Previous studies have suggested that children that are picky eaters may have a different and less varied diet than non-picky children, but the literature on picky eating in Chinese children is limited. Objectives: To assess the prevalence of picky eating in 6–35 month-old Chinese children, and to explore how parents' perceptions of picky eating relate to children's intake and body composition. Methods: 1414 6-35 month-old infants and toddlers from 8 Chinese cities were included in this study. Questionnaires were used to collect information on family demographic factors, child picky eating behaviors, food group rejection, and parents' perception of child weight status. Dietary intake data was collected via 24-h recall. Children's length/height and weight were measured. Results: The reported prevalence of picky eating was higher in 24–35 month-olds (36% of children) compared to 6-11 month-olds (12%). There were no consistent significant differences in dietary intakes of nutrients between picky and non-picky eaters. Picky eating children whose parents indicated that they avoided eggs or fruit had lower intakes of these food groups compared to non-picky eaters, whereas those reported to avoid meat had higher meat intakes. Weight status was underestimated by parents of both picky and non-picky children. Conclusions: Picky eating seems to occur at similar prevalence rates in China as has been reported in other countries. Parents' perceptions of food refusal do not reflect actual intakes, nor do nutrient intakes of picky eaters show additional gaps compared to non-picky eating children. In healthy children with typical growth patterns, picky eating seems to be a normal phase of development experienced by some children, without substantial consequences on their nutrient or food group intakes.